Role of the gut microbiome in frequent gut colonization with extended-spectrum β lactamase-producing Enterobacterales among Peruvian children - Maya L. Nadimpalli; Neha Sehgal; Luismarcelo Rojas-Salvatierra; Robert H. Gilman; Ashlee M. Earl; Colin J. Worby; Madison Schwab; Amy J. Pickering; Monica J. Pajuelo (Gut Microbes)
Gut colonization with extended-spectrum beta lactamase-producing Enterobacterales (ESBL-E) is increasingly common among children in low- and middle-income countries. Some children nevertheless remain never or rarely colonized during early life. Understanding how this protection is conferred could be helpful for designing future interventions to protect children’s health. Here, we investigated whether differences in gut microbiome development could underlie differential susceptibility to ESBL-E gut colonization over time among children in peri-urban Lima. Weekly stool and daily surveys were collected from 345 children < 3 years old during a 2016–19 study of enteric infections. A subset of children (n = 12) was rarely gut-colonized with ESBL-E from 1–16 months of age. We performed short-read metagenomic sequencing of stool collected at 3, 6, 7, 9, 12, and 16 months from these children and a random subset of 42 frequently colonized children, and characterized differences in their exposures and gut microbiomes. No differences in gut taxa or functional pathways were identified over time, though children harbored differentially abundant taxa, more unique E. coli strains, and a higher abundance of blaCTX-M gene copies at ESBL-E-positive versus negative timepoints. Differing patterns of ESBL-E colonization over time among children in peri-urban Lima do not appear to be related to differences in gut microbiome development.